1994
DOI: 10.1051/lait:1994633
|View full text |Cite
|
Sign up to set email alerts
|

Le lait de jument et sa production : particularités et facteurs de variation

Abstract: Résumé -Cette synthèse tente de faire ressortir les particularités de la production de lait des juments et de sa composition. Les juments allaitantes produisent en début de lactation entre 2 et 3,5 kg de lait par 100 kg de poids vif, ce qui est légèrement supérieur à la production des juments laitières et beaucoup plus élevé que celle des vaches allaitantes. Le lait est très pauvre en matières grasses, et les matières azotées se caractérisent par une proportion faible de caséines (50 à 60%). La différence moye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…From the 30th to the 120th post-foaling day, the milk produced by the first milking was 42% of the total daily amount. Other authors also observed that jennets Salimei et al, 2004) and mares (Doreau, 1991;Dell'Orto et al, 1994) produced more milk in the second milking than in the first one.…”
Section: Resultsmentioning
confidence: 81%
“…From the 30th to the 120th post-foaling day, the milk produced by the first milking was 42% of the total daily amount. Other authors also observed that jennets Salimei et al, 2004) and mares (Doreau, 1991;Dell'Orto et al, 1994) produced more milk in the second milking than in the first one.…”
Section: Resultsmentioning
confidence: 81%
“…Foals were physically separated from the dams 3 h before the first milking, following Doreau's [17] observations in milking nursing mares.…”
Section: General (Animals Housing and Feeding)mentioning
confidence: 99%
“…Its consumption, though extremely limited, has increased due to pediatric studies carried out over the last decade for the treatment of intolerance to cow's milk in young children [6,8,11]. It is not used, either fresh or after fermentation, in the diets of adults even if it has been suggested to have favorable pharmaceutical and nutritional properties [9,10,20]. Considering the numerous benefits of donkey's milk, including its healthpromoting characteristics and probiotic effects, Coppola et al [7] suggested the possibility of using donkey's milk for probiotic purposes.…”
Section: Introductionmentioning
confidence: 99%